O clique da notícia: a história da Folha Online contada por seu design - Lucena, Rodolfo Reckziegel de (2008)
Today, the internet provides vast resources for obtaining information. Newspapers, both online and print, present information to the reader that is deemed most important. Once the online newspaper has been able to capture the attention of the user, it must then be able to keep this reader's attention on what the newspaper feels is the most important information. In order to understand the mechanisms used in electronic journalism and how they are utilized on the electronic page, this work follows the work of Folha Online, the internet branch of Folha de S. Paulo, Brazil's largest circulation newspaper. Based on information gathered in books, newsprinted reports, the internet and especially of interviews with print journalists and web designers who took part in the creation of this service, the story of Folha Online is told through the analysis of its web pages. This work shows each of the forms adapted in the various layouts of Folha Online, comparing them to previous works, demonstrating the changes and discussing the rationale behind the changes with the designers and editors who took part in its creation. It also points out, by following the work that went into the creation of Folha Online, the editorial challenges which newsprint editors face in newsprint journalism in the coming years, from the affirmation of its own identity as a printed product to the question of its economic viability